P3.104 Lymphogranuloma Venereum: a descriptive study of the epidemiology and risk factors in british columbia, canada. (8th July 2017) - Wong, J; Hoang, L; Makaroff, S; Montgomery, C; Severini, A; Goldman, L; Gilbert, M; Grennan, T
Abstract : Introduction: Lymphogranuloma venereum (LGV) continues to be difficult to diagnose and can lead to significant sequelae. Since 2011, all rectal specimens testing positive for Chlamydia trachomatis were tested for LGV serovars, leading to a greater number of LGV cases (mean, 21 cases/year for 2011–2014). In 2015, case reports of LGV doubled to 42 cases. We sought to characterise LGV cases reported in BC since 2011, and assess possible reasons for the 2015 increase. Methods: Demographic and behavioural information about all LGV cases reported in BC from January 1, 2011 to December 31, 2015 were identified. Provincial laboratory data were reviewed for potentially missed cases. LGV cases were categorised by reporting year (i.e., 2011–2014 and 2015) and analysed using the chi-square test or Fisher's exact test. LGV percent positivity was calculated as the number of LGV cases over the number of positive rectal chlamydia. Results: From 2011–2014, 83 cases were reported versus 42 in 2015. All were among men who have sex with men (MSM). The median age for cases was 46 years and 44 years for 2011–2014 and 2015, respectively (p=0.26). HIV co-infection was similar in both periods (54/83 in 2011–2014, 25/42 in 2015, p=0.61). Of those known to be co-infected with HIV, the majority had undetectable viral loads (34/54 in 2011–2014 and 18/25 in 2015). There was a decrease in the proportion of cases who identified as Caucasian from 2011–2014 to 2015 (p=0.004) and an increase in proportion of asymptomatic cases, although not statistically significant (p=0.06). Percent positivity was 7.1% and 7.2% in 2011–2014 and 2015, respectively. Conclusion: The similar case characteristics and percent positivity during both periods, and increase in proportion of asymptomatic cases, suggest that increased screening for rectal sexually transmitted infections may be the reason for the observed increase in LGV cases. Further evaluation is needed to understand LGV trends, particularly among HIV-positive MSM who are disproportionately affected by LGV.